A comparative study on surgical outcomes of trabeculectomy with and without anti-metabolites in juvenile open-angle glaucoma - Vijayalakshmi A Senthilkumar; Sharmila Rajendrababu; Kondepati Kavya; Amit Pathak; Mohammed Sithiq Uduman (Indian Journal of Ophthalmology, 2023)
Purpose: To compare the surgical outcomes of trabeculectomy with and without anti-metabolites in patients with juvenile open-angle glaucoma (JOAG). Methods: This retrospective comparative case series included 98 eyes of 66 patients with JOAG who underwent either trabeculectomy without anti-metabolites (group A, n = 53 eyes) or with anti-metabolites (group B, n = 45 eyes) with a minimum of 2 years follow-up. The main outcome measures were intra-ocular pressure (IOP), number of glaucoma medications, visual acuity, additional surgical interventions, surgical complications, and risk factors for failure. Surgical failure was defined as IOP >18 mmHg or failure to reduce IOP by <30% from the baseline value or IOP ≤5 mmHg or re-operation for refractory glaucoma or a complication or loss of light perception vision. Results: The mean post-operative IOP reduced significantly from baseline at all post-operative visits until 6 months and thereafter. The cumulative probability of failure at 2 years was 28.7% in group A [95% confidence interval (CI) = 17.6–44.8%] and 29.1% in group B (95% CI = 17.1–46.7%) (P = 0.78). Surgical complications occurred in 18 eyes (34%) in group A and 19 eyes (42%) in group B. Re-operations for glaucoma or complications were performed in two eyes (3.8%) in group A and two eyes (4.4%) in group B. Cox-hazard regression model revealed male gender (HR = 0.29; P = 0.008), baseline high IOP (HR = 0.95; P = 0.002), and an increased number of pre-operative glaucoma medications (HR = 2.08; P = 0.010) as significant factors associated with failure. Conclusion: Our study results on trabeculectomy in JOAG revealed a success of 71% in both groups at 2 years follow-up. There was no significant difference in success or failure rates between the two groups. The risk factors for poor surgical outcome in JOAG were male gender, baseline high IOP, and an increased number of glaucoma medications.